Preliminary dismissal of claimin the «New» Code of Constitutional Procedure - Avalos Pretell, Bruno Fernando (2022)
This paper develops the diverse positions that have been presented from the new regulation referring to the prohibition of preliminary dismissal in protection proceedings, habeas corpus, habeas data and compliance, derived from both doctrine, jurisprudence and legislative sieve. It also explains the various legal concepts and categories in connection with the new regulation, such as judicial independence, the fundamental right to access to justice, the preliminary dismissal of the claim, the role of the judge as director of the proceedings, and the constitutionality of the regime of preliminary control of the claim. Finally, an interpretative formula is proposed for section 6 of the New Code of Constitutional Procedure, so that it be related to the Constitution.